Application of the Technology Readiness Index to Measure the Readiness of Personnel Information Systems for Village Employees in Tanjungmedar District - Guntara, Agun; Fadil, Irfan; Supriadi, Fidi; Mulyana, Aa Agus (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2025)
The development of information technology encourages village governments to adopt digital systems in improving services, including in the field of staffing. However, the readiness of village officials in using this information system is often a major challenge. This study aims to measure the level of readiness of village officials in Tanjungmedar District in adopting a personnel information system using the Technology Readiness Index (TRI) model. This model analyzes four psychological dimensions, namely optimism, innovativeness, discomfort, and insecurity. The study involved all village officials in nine villages in Tanjungmedar District with a total of 96 respondents. Data were collected through a Likert scale-based questionnaire and analyzed using validity, reliability, and TRI calculations. The research results showed a total TRI score of 3.38, which falls into the medium readiness index category. The variables of optimism and innovation received high scores, 1.02 and 1.03 respectively, while discomfort and insecurity scored lower, at 0.66 and 0.68. The research results indicate the need to improve aspects of comfort and security in the use of the information system. As a recommendation, technical training and system improvements are suggested to support optimal adaptation of information technology.